Solid electrolyte composition, solid electrolyte formed therefrom, and lithium secondary battery comprising same
By using a solid electrolyte composition of amine compounds, polyfunctional isocyanates and lithium salts to form a network structure and dynamic covalent bonds, the problems of lithium dendrites and liquid electrolyte stability in lithium-ion batteries are solved, and high ionic conductivity and electrochemical stability at low temperatures are achieved, making it suitable for applications such as electric vehicles.
Patent Information
- Application Number
- CN202380070745.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-05
- Filing Date
- 2023-09-27
- Publication Date
- 2025-09-16
AI Technical Summary
Existing lithium-ion batteries use lithium metal negative electrodes, which lead to lithium dendrites and reduced battery performance. The use of flammable liquid electrolytes also results in low battery stability. In addition, all-solid-state batteries have low ionic conductivity at low temperatures, affecting the battery output characteristics and electrochemical properties.
A solid electrolyte composition containing an amine compound, a multifunctional isocyanate and a lithium salt is used to form a network structure and dynamic covalent bonds, thereby inhibiting crystallization, improving the mobility and electrochemical stability of lithium ions, and using glass-like polymer properties to maintain high ionic conductivity at low temperatures.
It inhibits electrolyte crystallization at low temperatures, improves the mobility and electrochemical stability of lithium ions, and enhances the stability and output characteristics of lithium secondary batteries, making them suitable for applications such as electric vehicles.
Smart Images

Figure CN120660217A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolyte composition, a solid electrolyte formed from the solid electrolyte, and a lithium secondary battery containing the solid electrolyte. Specifically, the present invention relates to a solid electrolyte, a composition for forming the solid electrolyte, and a lithium secondary battery containing the solid electrolyte. Since the solid electrolyte is inhibited from crystallizing at low temperatures, the low-temperature output characteristics of the secondary battery are improved, and the electrochemical stability is enhanced. Background Art
[0002] Currently, various approaches are being explored to increase the energy density of lithium-ion batteries, one of which is the use of lithium metal in the negative electrode. However, lithium-ion batteries using lithium metal negative electrodes suffer from a significant performance degradation due to the formation of lithium dendrites during charge and discharge. Furthermore, existing lithium-ion batteries suffer from low stability due to their use of flammable liquid electrolytes. To improve this, research is underway into all-solid-state batteries using solid electrolytes with high ionic conductivity and electrochemical stability.
[0003] Generally speaking, in all-solid-state batteries, linear polymers or cross-linked polymers of homopolymers or copolymers with ethylene oxide as the basic unit are mainly used as ion-conductive polymers for forming solid electrolytes. Such polymers are easy to crystallize, resulting in low ion conductivity at low temperatures, thereby reducing the output characteristics and electrochemical characteristics of the all-solid-state battery.
[0004] Therefore, there is a need to develop a solid electrolyte with improved output characteristics at low temperatures and excellent ion conductivity.
[0005] [Prior art literature]
[0006] [Patent Document]
[0007] (Patent Document 1) Patent Publication No. 10-2023-0018141 (2023.02.07) Summary of the Invention
[0008] Technical issues
[0009] The present invention aims to solve the above-mentioned problems. The purpose of the present invention is to provide a solid electrolyte composition and a solid electrolyte formed therefrom, wherein the lithium ion mobility in the solid electrolyte composition is improved, crystallization at low temperatures is suppressed, ionic conductivity is excellent, and electrochemical stability is excellent.
[0010] An object of the present invention is to provide a lithium secondary battery having excellent output characteristics at low temperatures, electrochemical stability, and safety due to the introduction of the above-mentioned solid electrolyte.
[0011] Technical Solution
[0012] To solve the above problems, the present invention provides a solid electrolyte composition comprising: an amine compound represented by Chemical Formula 1;
[0013] Polyfunctional isocyanates; and
[0014] lithium salts,
[0015] Wherein, based on 100 parts by weight of the amine compound, the content of the lithium salt is 40 to 80 parts by weight.
[0016] [Chemical Formula 1]
[0017]
[0018] In the chemical formula 1, L1 and L2 each independently include a group selected from C1-C 12 Alkylene or heteroalkylene, C3-C 16 Cycloalkylene or heterocycloalkylene, C6-C 16 Arylene or heteroarylene and At least one of the following, wherein n is a natural number in the range of 1 to 5000, and m is a natural number in the range of 1 to 200.
[0019] In this case, the polyfunctional isocyanate may be one or more selected from triphenylmethane-4,4,4-triisocyanate, 1,3,5-triisocyanato-2-methylbenzene, tris(6-isocyanatohexyl)isocyanurate, 1,3,5-triisocyanato-2,4,6-trimethylbenzene, and poly(hexamethylene diisocyanate).
[0020] In addition, the content of the polyfunctional isocyanate may be 5 to 20 parts by weight based on 100 parts by weight of the amine compound.
[0021] On the other hand, the lithium salt may include one or more selected from lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium nitrate (LiNO3), and lithium hexafluorophosphate (LiPF6).
[0022] The present invention may also provide a solid electrolyte comprising a solidified product of the solid electrolyte composition.
[0023] In one example, the solid electrolyte of the present invention has at least two inflection points in a curve of thermal strain versus temperature measured by dilatometry.
[0024] In another example, the solid electrolyte of the present invention may have a topology freezing transition temperature (Tv) higher than the glass transition temperature (Tg) measured by dilatometry.
[0025] In one embodiment of the present invention, a lithium secondary battery may be provided, comprising: the above-mentioned solid electrolyte; a positive electrode; and a negative electrode.
[0026] Beneficial effects
[0027] The solid polymer electrolyte of the present invention has suppressed crystallization, thereby improving lithium ion mobility, increasing ion conductivity, and having excellent electrochemical stability, thereby contributing to improved stability and output of lithium secondary batteries.
[0028] The lithium secondary battery of the present invention has excellent output characteristics at low temperatures and is excellent in electrochemical stability and safety, and therefore has characteristics suitable for electric vehicles and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 3 is a diagram showing the Nyquist plot of the solid electrolyte in Example 1.
[0030] Figure 2 Graph showing the LSV measurement results of the solid electrolyte produced in Example 1.
[0031] Figure 3 Graph showing the LTN measurement results of Example 1.
[0032] Figure 4 Graph showing a curve of thermal strain (Strain) versus temperature measured by dilatometry for the solid electrolyte in Example 1.
[0033] Figure 5 A diagram showing the experimental process in Experimental Example 2. DETAILED DESCRIPTION
[0034] Before describing the present invention in more detail, the meanings of the terms used in this specification are defined.
[0035] In this specification, "alkyl group" refers to a monovalent aliphatic hydrocarbon group. The alkyl group includes straight-chain (unbranched) and branched (branched). When an alkyl group with a specific number of carbon atoms is specified, it may be intended to encompass all geometric isomers with that number of carbon atoms. Thus, for example, "butyl" may be intended to encompass n-butyl, sec-butyl, isobutyl, tert-butyl, and cyclobutyl, and "propyl" may be intended to encompass n-propyl, isopropyl, and cyclopropyl. Examples of the alkyl group include one or more selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, n-pentyl, and n-hexyl, but are not limited thereto.
[0036] In the present specification, "cycloalkyl" refers to a monovalent aliphatic cyclic hydrocarbon group. The cycloalkyl group may include, for example, one or more selected from cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, and cyclodecyl, but is not limited thereto.
[0037] In addition, in this specification, "alkylene group" refers to a divalent aliphatic hydrocarbon group. The alkylene group is, for example, one selected from methylene, ethylene, propylene, butylene, pentylene, and hexylene, but is not limited thereto.
[0038] In this specification, "cycloalkylene group" refers to a divalent aliphatic cyclic hydrocarbon group. It is independent of the position of the divalent linker arm. For example, it can be selected from 1,2-cycloalkylene, 1,3-cycloalkylene, 1,4-cycloalkylene and 1,5-cycloalkylene. The cycloalkylene group can be, for example, selected from 1,2-cyclobutylene, 1,3-cyclobutylene, 1,2-cyclopentylene, 1,3-cyclopentylene, 1,2-cyclohexylene, 1,3-cyclohexylene, 1,4-cyclohexylene, 1,2-cycloheptylene, 1,3-cycloheptylene, 1,4-cycloheptylene, 1,2-cyclooctylene, 1,3-cyclooctylene, 1,4-cyclooctylene and 1,5-cyclooctylene, but is not limited thereto.
[0039] In the present specification, the term "heteroalkyl group" refers to an alkyl group in which one or more carbon atoms in the carbon chain are substituted with a heteroatom.
[0040] In this specification, "heteroalkylene group" means that one or more carbon atoms in the carbon chain of the alkylene group are replaced by heteroatoms. a ~C b The heteroalkylene group refers to a heteroalkylene group having a to b carbon atoms in the heteroalkylene group.
[0041] In the present specification, the term "heterocycloalkylene group" refers to a group in which one or more carbon atoms in a cycloalkyl carbon chain are substituted with a heteroatom.
[0042] In the present specification, "heteroatom" may refer to an atom other than carbon and hydrogen, and may include, for example, oxygen, nitrogen, sulfur, etc., but is not limited thereto.
[0043] In this specification, "aryl group" refers to an aromatic substituent that is a monovalent covalent π-electron system, including a monocyclic ring or a polycyclic ring with more than two rings, and all elements of the ring are composed of carbon. Aryl groups include substituted or unsubstituted aromatic groups. Examples of aryl groups include
[0044] as well as But it’s not limited to this.
[0045] In the present specification, an "arylene group" refers to a divalent aromatic substituent further having one linking arm in the aryl group.
[0046] In this specification, "heteroaryl group" refers to an aromatic substituent having a monovalent covalent π electron system, wherein at least one of the atoms forming the ring is a heteroatom. Examples of heteroaryl groups may include
[0047] as well as etc., but not limited to.
[0048] Among them, R m H, C 1-20 Alkyl or C3 to C 14 Heteroaryl.
[0049] In the present specification, a "heteroarylene group" refers to an aromatic substituent having a divalent covalent π-electron system, and the heteroarylene group further has one linking arm.
[0050] In this specification, "vitrimer" refers to a substance that exhibits both the chemical stability of a thermosetting polymer and the processability of a thermoplastic polymer.
[0051] In this specification, "topological freezing transition temperature (Tv)" refers to the temperature at which a dynamic reversible reaction occurs rapidly in a "glass-like polymer". At Tv or higher, the topology can be rearranged, while at temperatures below Tv, the dynamic reversible reaction proceeds very slowly, resulting in typical thermosetting properties.
[0052] The present invention will be described in further detail below with reference to specific embodiments. This is not intended to limit the technology described in this specification to specific embodiments, but should be understood to include various modifications, equivalents, and / or alternatives to the embodiments of the present invention. In the description of the drawings, similar reference numerals may be used for similar components.
[0053] In addition, in order to clearly describe the present invention in the drawings, parts irrelevant to the description are omitted, and the thickness is exaggerated to clearly express each layer and region. The same symbols may be used to describe components with the same function within the same concept.
[0054] In this specification, expressions such as "have", "may have", "include", or "may include" refer to the existence of the feature (for example, a value, function, operation, or component, etc.) and do not exclude the existence of additional features.
[0055] In this specification, expressions such as "A or B", "at least one of A or / and B", or "one or more of A or / and B" may include all possible combinations of the items listed together. For example, "A or B", "at least one of A and B", or "at least one of A or B" may refer to all cases of (1) including at least one A, (2) including at least one B, or (3) including at least one A and at least one B.
[0056] Hereinafter, the technical features and effects of the present invention will be described in detail.
[0057] 1. Solid electrolyte composition
[0058] The inventors of the present invention developed the present invention to solve the problem of reduced secondary battery output due to crystallization of ion-conductive polymers at low temperatures in existing solid electrolytes for all-solid-state batteries, resulting in a significant decrease in ion conductivity at low temperatures.
[0059] In one embodiment of the present invention, the solid electrolyte composition of the present invention may include an amine compound represented by Chemical Formula 1, a polyfunctional isocyanate, and a lithium salt, wherein the content of the lithium salt is 40 to 80 parts by weight based on 100 parts by weight of the amine compound.
[0060] [Chemical Formula 1]
[0061]
[0062] In the chemical formula 1, L1 and L2 each independently include a group selected from C1-C 12 Alkylene or heteroalkylene, C3-C 16 Cycloalkylene or heterocycloalkylene, C6-C 16 Arylene or heteroarylene and At least one of the following, wherein n is a natural number in the range of 1 to 5000, and m is a natural number in the range of 1 to 200.
[0063] 1) Amine compounds
[0064] The solid electrolyte of the present invention may include an amine compound represented by Chemical Formula 1.
[0065] [Chemical Formula 1]
[0066]
[0067] In the chemical formula 1, L1 and L2 each independently include a group selected from C1-C 12 Alkylene or heteroalkylene, C3-C 16 Cycloalkylene or heterocycloalkylene, C6-C 16 Arylene or heteroarylene and At least one of the following, wherein n is a natural number in the range of 1 to 5000, and m is a natural number in the range of 1 to 200.
[0068] Preferably, in the chemical formula 1, L1 and L2 can be The n is a natural number in the range of 20 to 3000, and m is a natural number in the range of 1 to 10.
[0069] Most preferably, the amine compound can be represented by Chemical Formula 2.
[0070] [Chemical Formula 2]
[0071]
[0072] In the chemical formula 2, p may be a natural number within the range of 1 to 5000, preferably 20 to 3000, and more preferably 40 to 2000.
[0073] The amine compound may include a thiourea structure in the main chain. The thiourea structure can induce a nonlinear structure through interaction with heteroatoms of the solid electrolyte described later, and can form dynamic covalent bonds capable of bond exchange. As a result, the electrolyte formed from the solid electrolyte composition containing the amine compound can simultaneously have high flexibility and excellent self-healing properties.
[0074] The weight average molecular weight of the compound represented by Chemical Formula 1 may be 1,000 to 1,000,000 g / mol, preferably 3,000 to 700,000 g / mol, and more preferably 5,000 to 400,000 g / mol.
[0075] When the weight average molecular weight of the compound represented by Chemical Formula 1 is less than 1000 g / mol, the mechanical properties of the solid electrolyte decrease, resulting in a decrease in the electrochemical stability of the electrolyte. When it is greater than 1000000 g / mol, the ionic conductivity of the electrolyte decreases and the crystallization temperature at low temperatures increases, resulting in a decrease in battery output.
[0076] 2) Polyfunctional isocyanate
[0077] The solid electrolyte composition of the present invention may include a polyfunctional isocyanate. The polyfunctional isocyanate may form a urea bond by bonding with the amine group in the compound of Chemical Formula 1, and a network structure may be formed through the plurality of urea bonds.
[0078] In the present invention, the polyfunctional isocyanate may be one or more selected from triphenylmethane-4,4,4-triisocyanate, 1,3,5-triisocyanato-2-methylbenzene, tris(6-isocyanatohexyl)isocyanurate, 1,3,5-triisocyanato-2,4,6-trimethylbenzene and poly(hexamethylene diisocyanate), preferably poly(hexamethylene diisocyanate).
[0079] In one example, based on 100 parts by weight of the amine compound, the content of the polyfunctional isocyanate in the solid electrolyte composition of the present invention may be 5 to 20 parts by weight, preferably 8 to 18 parts by weight, and more preferably 10 to 15 parts by weight.
[0080] Based on 100 parts by weight of the amine compound, when the content of the multifunctional isocyanate is less than 5 parts by weight, a sufficient cross-linking network cannot be formed, resulting in the inability to form a solid electrolyte, and when it is greater than 20 parts by weight, the cross-linking density becomes too high, resulting in low ionic conductivity.
[0081] 3) Lithium salts
[0082] The lithium salt can be used as an electrolyte salt in a lithium secondary battery. The lithium salt can be used as a medium for transferring ions and includes lithium cations (Li + ) and selected from F - 、Cl - Br - , I - 、NO3 - 、N(CN)2 - 、ClO4 - 、BF4 - 、AlO4 - 、AlCl4 - PF6 - 、SbF6 - 、AsF6 - 、BF2C2O4 - BC4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - 、C4F9SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - More than one anion in, but not limited to.
[0083] Examples of the lithium salt may include one or more selected from lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO 4 ), lithium nitrate (LiNO 3 ), and lithium hexafluorophosphate (LiPF 6 ), but are not limited thereto.
[0084] Based on 100 parts by weight of the amine compound, the content of the lithium salt may be 40 to 80 parts by weight, preferably 45 to 75 parts by weight, and more preferably 60 to 70 parts by weight.
[0085] The solid polymer electrolyte composition of the present invention can ensure high lithium cation (Li + ) and achieves a reduction effect on the diffusion resistance of lithium ions, thereby improving the cycle capacity characteristics.
[0086] In the present invention, when the lithium salt content is less than 40 parts by weight based on 100 parts by weight of the amine compound, sufficient lithium ion conductivity is difficult to ensure due to the relatively low lithium content. Furthermore, when the lithium salt content exceeds 80 parts by weight based on 100 parts by weight of the amine compound, the lithium salt cannot be solvated in the polymer matrix, and a large amount of lithium salt is present to form ion pairs, resulting in no significant improvement in the effect and disadvantageous in terms of economic efficiency. Therefore, it is preferred to adjust the content within the above range according to the intended purpose.
[0087] 4) Solvent
[0088] In a preferred embodiment of the present invention, the solid polymer electrolyte composition may further comprise an organic solvent to adjust the viscosity or improve the solubility between the monomers used. Available organic solvents include tetrahydrofuran (THF), 2-methyltetrahydrofuran, dimethylformamide (DMF), acetonitrile, N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), dimethylacetamide (DMAc), dichloromethane, acetone, isopropyl alcohol, methyl ethyl ketone (MEK), and the like, but are not limited thereto. One or more of these may be selected for use.
[0089] 5) Catalyst
[0090] In one example, the solid electrolyte composition of the present invention may further include a catalyst, and the catalyst may be an alkali catalyst.
[0091] Examples of the base catalyst include at least one selected from dibutyltin dilaurate, 1,5,7-Triazabicyclo[4.4.0]dec-5-ene (TBD), 1,8-Diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5-Diazabicyclo[4.3.0]non-5-ene (DBN), 4-Dimethylaminopyridine (DMAP), triethylamine (TEA), tributylamine (TBA), and trioctylamine (TOA), but are not limited thereto.
[0092] When the solid electrolyte composition of the present invention includes an alkali catalyst, the content of the alkali catalyst may be in the range of 0.1 wt % to 5 wt % based on the total composition.
[0093] 2. Solid electrolyte
[0094] Furthermore, the present invention provides a solid electrolyte comprising a solidified product of the solid electrolyte composition.
[0095] In one example, the solid electrolyte of the present invention has at least two inflection points in a curve of thermal strain versus temperature measured by dilatometry.
[0096] As described above, the solid electrolyte of the present invention may include a network structure formed by dynamic bonding, and therefore, the solid electrolyte of the present invention may have different properties from conventional thermosetting polymers. For one, the solid electrolyte of the present invention may have two transition temperatures. Figure 4 The following is a curve showing the change of thermal strain (Strain) with temperature measured by dilatometry for the solid electrolyte of the embodiment of the present invention. Figure 4 As shown, the solid electrolyte of the present invention may have two inflection points in a curve of thermal strain versus temperature measured by dilatometry.
[0097] The inflection point may indicate that the solid electrolyte of the present invention has obvious physical properties at different temperatures, and may indicate that it has two transition temperatures. One of them may be the glass transition temperature (Tg), that is, the temperature at which the polymer chain undergoes segmental motion and changes from a rigid state to a formable state, and the other may be the topological freezing transition temperature (Tv), that is, the temperature at which the polymer changes from a viscoelastic solid to a liquid due to rapid bond exchange. The solid electrolyte of the present invention has a topological freezing transition temperature (Tv), that is, it has the characteristics of a so-called glass-like polymer (vitrimer), and has self-healing ability while having high ionic conductivity.
[0098] In addition, if Figure 4 As shown in FIG5 , in the relationship between the glass transition temperature (Tg) and the topology freezing transition temperature (Tv) measured by dilatometry, the topology freezing transition temperature (Tv) of the solid electrolyte of the present invention may be higher than the glass transition temperature (Tg).
[0099] The method for producing the solid polymer is not particularly limited, and the monomers in the composition may be polymerized and cross-linked by methods known in the art to thereby solidify the composition.
[0100] Specifically, the solid electrolyte may be manufactured by coating the solid electrolyte composition on the surface of a membrane or an electrode and curing the solid electrolyte composition by irradiating ultraviolet rays, or curing the solid electrolyte composition by heat treatment.
[0101] As the coating method, a known coating method such as slit coating, gravure coating, spin coating, direct spray coating, drum coating, cast coating, screen printing, inkjet printing, etc. can be used.
[0102] The solid electrolyte of the present invention produced by this method can also exhibit high ionic conductivity at low temperatures.
[0103] 4. Lithium secondary battery
[0104] Furthermore, the present invention provides a lithium secondary battery comprising: a positive electrode; a negative electrode; and the solid electrolyte of the present invention.
[0105] The lithium secondary battery can be manufactured by a conventional method known in the art, for example, by coating the solid electrolyte composition on a positive electrode, curing the composition, and stacking a negative electrode.
[0106] 1) Positive electrode
[0107] The positive electrode collector is not particularly limited as long as it does not cause chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, or a collector treated with carbon, nickel, titanium, silver, etc. on the surface of aluminum or stainless steel can be used.
[0108] The positive electrode active material is a compound that can reversibly insert and remove lithium, and can be a lithium composite metal oxide comprising one or more metals such as cobalt, manganese, nickel or aluminum and lithium. More specifically, the lithium composite metal oxide includes lithium manganese oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium cobalt oxides (e.g., LiCoO2, etc.), lithium nickel oxides (e.g., LiNiO2, etc.), lithium nickel manganese oxides (e.g., LiNi 1-Y Mn Y O2 (where 0<Y<1), LiMn 2- z Ni z O4 (where 0<Z<2), etc.), lithium nickel cobalt oxides (e.g., LiNi 1-Y1 Co Y1 O2 (where 0<Y1<1), etc.), lithium manganese cobalt oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0<Y2<1), LiMn 2-z1 Co z1 O4 (where 0 < Z1 < 2), etc.), lithium manganese cobalt oxides (e.g., Li(Ni p Co q Mn r1 )O2 (where 0<p<1, 0<q<1, 0<r1<1, p+q+r1=1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0<p1<2, 0<q1<2, 0<r2<2, p1+q1+r2=2), etc.), or lithium nickel cobalt-transition metal (M) oxide (e.g., Li(Ni p2 Co q2 Mn r3 M S2 )O2 (wherein, M is selected from Al, Fe, V, Cr, Ti, Ta, Mg and Mo, p2, q2, r3, s2 are the atomic fractions of independent elements and are 0<p2<1, 0<q2<1, 0<r3<1, 0<s2<1, p2+q2+r3+s2=1)), etc., and may include any one or two or more compounds thereof.
[0109] In order to improve the capacity characteristics and stability of the battery, the lithium composite metal oxide can be LiCoO2, LiMnO2, LiNiO2Li, lithium nickel manganese cobalt oxide (for example, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2、Li(Ni 0.6 Mn 0.2 Co 0.2 )O2、Li(Ni 0.5 Mn 0.3 Co 0.2 )O2、Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc., or lithium nickel cobalt aluminum oxide (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.).
[0110] Based on the total weight of the solid components in the positive electrode slurry, the content of the positive electrode active material may be 80 wt % to 99 wt %.
[0111] The binder is a component that helps to bind the active material to the conductive material and the current collector. It is usually added in an amount of 1 to 30% by weight based on the total weight of the solid components in the positive electrode slurry. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers.
[0112] Typically, 1 to 30 wt % of the conductive material is added based on the total weight of the solid components in the positive electrode slurry.
[0113] Such conductive materials are not particularly limited as long as they do not cause chemical changes in the battery and have conductivity. For example, carbon powders such as carbon black, acetylene black (or Denka Black), Ketjen black, channel black, furnace black, lamp black, and thermal black can be used; graphite powders such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0114] The positive electrode slurry may include a solvent. The solvent may include an organic solvent such as N-methyl-2-pyrrolidone (NMP), and can be used in an amount to achieve a desired viscosity when the positive electrode active material and optionally a binder and a conductive material are included. For example, the solid content concentration in the slurry containing the positive electrode active material and optionally a binder and a conductive material can reach 50% by weight to 95% by weight, preferably 70% by weight to 90% by weight.
[0115] 2) Negative electrode
[0116] The negative electrode can be manufactured by forming a negative electrode composite layer on a negative electrode current collector. The negative electrode composite layer can be formed by coating a negative electrode slurry containing a negative electrode active material, a binder, a conductive material, and a solvent on the negative electrode current collector, followed by drying and rolling.
[0117] The negative electrode current collector typically has a thickness of 3 to 500 μm. This negative electrode current collector is not particularly limited, as long as it does not cause chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, or current collectors treated with carbon, nickel, titanium, silver, or the like on the surface of copper or stainless steel, as well as aluminum-cadmium alloys, can be used. Furthermore, similar to the positive electrode current collector, fine surface irregularities can be formed to enhance the binding force of the negative electrode active material. The negative electrode current collector can be used in various forms, such as films, sheets, foils, meshes, porous bodies, foams, and non-woven fabrics.
[0118] In addition, the negative electrode active material may include at least one selected from lithium metal, carbon materials capable of reversibly intercalating and deintercalating, metals or alloys of these metals and lithium, metal composite oxides, materials capable of doping and dedoping lithium, and transition metal oxides.
[0119] The carbon material capable of reversibly intercalating and deintercalating lithium is not particularly limited, and any carbon-based negative electrode active material commonly used in lithium-ion secondary batteries can be used, and representative examples may include crystalline carbon, amorphous carbon, or both. As the crystalline carbon, graphite such as natural graphite or artificial graphite in amorphous, plate-like, flaky, spherical, or fibrous form may be included, and as the amorphous carbon, soft carbon (low-temperature sintered carbon) or hard carbon, mesophase pitch carbide, calcined coke, etc. may be included.
[0120] The metal composite oxide can be selected from PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, LixFe2O3 (0≤x≤1), Li x WO2(0≤x≤1), and Sn x Me 1-x Me′ y O z (Me: Mn, Fe, Pb, Ge; Me′: Al, B, P, Si, elements of Groups 1, 2 and 3 of the periodic table, halogen; 0<x≤1; 1≤y≤3; 1≤z≤8).
[0121] The material capable of lithium doping and dedoping may include Si, SiO x (0<x≤2), Si-Y alloy (the Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, but not Si), Sn, SnO2, Sn-Y (the Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, but not Sn), etc., and at least one of them can also be mixed with SiO2 for use. The element Y may be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.
[0122] Examples of the transition metal oxide may include lithium-containing titanium composite oxide (LTO), vanadium oxide, and lithium vanadium oxide.
[0123] Based on the total weight of the solid components in the negative electrode slurry, the content of the negative electrode active material may be 80 wt % to 99 wt %.
[0124] The binder is a component that helps to bind the conductive material, active material and current collector. Generally, 1 to 30% by weight is added based on the total weight of the solid components in the negative electrode slurry. Examples of such binders may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers thereof.
[0125] The conductive material is a component used to further improve the conductivity of the negative electrode active material and can be added in an amount of 1 to 20% by weight based on the total weight of the solid components in the negative electrode slurry. This conductive material can be the same as or different from the conductive material used to manufacture the positive electrode, and can include, for example, carbon powders such as carbon black, acetylene black (or Denka Black), Ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powders such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0126] The negative electrode slurry may further include a solvent. The solvent may include an organic solvent such as NMP or alcohol, and may be used in an amount to achieve a desired viscosity when the negative electrode active material and, optionally, a binder and a conductive material are included. For example, the solid content concentration of the slurry containing the negative electrode active material and, optionally, a binder and a conductive material may be 50% to 95% by weight, preferably 70% to 90% by weight.
[0127] The advantages of a lithium secondary battery comprising the positive electrode and negative electrode as described above and the solid electrolyte of the present invention are that the electrochemical stability of the solid polymer electrolyte is maintained, and the battery output is not significantly reduced due to the inhibition of electrolyte crystallization at low temperatures, while maintaining excellent lithium ion mobility and ion conductivity.
[0128] Implementation Method
[0129] The present invention is further described in detail below through specific examples. However, this does not mean that the scope of the present invention is limited to the scope of the examples. The examples are merely specific application examples of the present invention to facilitate understanding. Those skilled in the art will understand that the same technical concept can be achieved by changing, deleting, or adding features within the scope of the claims.
[0130] Preparation Example: Synthesis of Thiourea Compounds
[0131] 50 mL of anhydrous DMF (dimethylformamide) and 15.5 g of BAEE (1,2-bis(2-aminoethoxy)ethane) were added sequentially to a vial containing a magnetic stir bar. Then, 17.8 g of TCDI (1,1′-thiocarbonyldiimidazole) was added with stirring. The flask was sealed and stirred at 25°C for 24 hours. The solution was then diluted with 100 mL of chloroform and precipitated into an excess of diethyl ether (1.5 L). The dissolution-precipitation process was repeated three times. The resulting precipitate was degassed and dried overnight at 140°C under vacuum to yield a yellow solid (13 g, 65%, PTU (polythiourea)) with a weight-average molecular weight of approximately 14,000 g / mol.
[0132] Example 1
[0133] A polymer electrolyte was prepared by adding an isocyanate crosslinker and a lithium salt to polythiourea. 0.2 g (100 parts by weight) of PTU prepared in the manufacturing example was dissolved in 2 mL of DMF, 0.025 g (12.5 parts by weight) of PHDI (polyhexamethylene diisocyanate; viscosity: 1300-2200 cP (25°C)) and 0.001 g of DD (dibutylyin dilaurate) were added, and the mixture was stirred evenly. Then, 0.125 g (62.5 parts by weight) of LiTFSI (lithium bis(trifluoromethanesulfonyl)imide) was added. The mixture was placed on a Teflon plate (2×4 cm) and the mixture was stirred evenly. 2 ), degassed and dried in a vacuum oven at 30° C., dried in a vacuum oven at 60° C. for 24 hours, and cured at 100° C. for 24 hours to produce a solid electrolyte membrane with a thickness of 150 μm.
[0134] Example 2
[0135] A polymer electrolyte was prepared by adding an isocyanate crosslinker and a lithium salt to polythiourea. 0.2 g (100 parts by weight) of PTU prepared in the manufacturing example was dissolved in 2 mL of DMF, 0.025 g (12.5 parts by weight) of PHDI (poly(hexamethylene diisocyanate); viscosity: 1300-2200 cP (25°C)) and 0.001 g of DD (dibutyltin dilaurate) were added, and the mixture was stirred evenly. 0.16 g (80 parts by weight) of LiTFSI (lithium bis(trifluoromethanesulfonyl imide)) was then added. The mixture was placed on a Teflon plate (2×4 cm 2 ), degassed and dried in a vacuum oven at 30°C. After vacuum drying at 60°C for 24 hours, the solution was cured at 100°C for 24 hours to produce a solid electrolyte membrane with a thickness of 150 μm.
[0136] Example 3
[0137] A polymer electrolyte was prepared by adding an isocyanate crosslinker and a lithium salt to polythiourea. 0.2 g (100 parts by weight) of PTU prepared in the manufacturing example was dissolved in 2 mL of DMF, 0.025 g (12.5 parts by weight) of PHDI (poly(hexamethylene diisocyanate); viscosity: 1300-2200 cP (25°C)) and 0.001 g of DD (dibutyltin dilaurate) were added, and the mixture was stirred evenly. 0.08 g (40 parts by weight) of LiTFSI (lithium bis(trifluoromethanesulfonyl imide)) was then added. The mixture was placed on a Teflon plate (2×4 cm 2 ), degassed and dried in a vacuum oven at 30° C., dried in a vacuum oven at 60° C. for 24 hours, and cured at 100° C. for 24 hours to produce a solid electrolyte membrane with a thickness of 150 μm.
[0138] Example 4
[0139] A polymer electrolyte was prepared by adding an isocyanate crosslinker and a lithium salt to polythiourea. 0.2 g (100 parts by weight) of PTU prepared in the manufacturing example was dissolved in 2 mL of DMF, 0.01 g (5 parts by weight) of PHDI (poly(hexamethylene diisocyanate); viscosity: 1300-2200 cP (25°C)) and 0.001 g of DD (dibutyltin dilaurate) were added, and the mixture was stirred evenly. 0.125 g (62.5 parts by weight) of LiTFSI (lithium bis(trifluoromethanesulfonyl imide)) was then added. The mixture was placed on a Teflon plate (2×4 cm 2 ), degassed and dried in a vacuum oven at 30° C., dried in a vacuum oven at 60° C. for 24 hours, and cured at 100° C. for 24 hours to produce a solid electrolyte membrane with a thickness of 150 μm.
[0140] Example 5
[0141] A polymer electrolyte was prepared by adding an isocyanate crosslinker and a lithium salt to polythiourea. 0.2 g (100 parts by weight) of PTU prepared in the manufacturing example was dissolved in 2 mL of DMF, 0.04 g (20 parts by weight) of PHDI (poly(hexamethylene diisocyanate); viscosity: 1300-2200 cP (25°C)) and 0.001 g of DD (dibutyltin dilaurate) were added, and the mixture was stirred evenly. 0.125 g (62.5 parts by weight) of LiTFSI (lithium bis(trifluoromethanesulfonyl imide)) was then added. The mixture was placed on a Teflon plate (2×4 cm 2 ), degassed and dried in a vacuum oven at 30° C., dried in a vacuum oven at 60° C. for 24 hours, and cured at 100° C. for 24 hours to produce a solid electrolyte membrane with a thickness of 150 μm.
[0142] Comparative Example 1
[0143] A polymer electrolyte was prepared by adding an isocyanate crosslinker and a lithium salt to polythiourea. 0.2 g (100 parts by weight) of PTU prepared in the manufacturing example was dissolved in 2 mL of DMF, 0.025 g (12.5 parts by weight) of PHDI (poly(hexamethylene diisocyanate); viscosity: 1300-2200 cP (25°C)) and 0.001 g of DD (dibutyltin dilaurate) were added, and the mixture was stirred evenly. 0.18 g (90 parts by weight) of LiTFSI (lithium bis(trifluoromethanesulfonyl imide)) was then added. The mixture was placed on a Teflon plate (2×4 cm 2 ), degassed and dried in a vacuum oven at 30° C., dried in a vacuum oven at 60° C. for 24 hours, and cured at 100° C. for 24 hours to produce a solid electrolyte membrane with a thickness of 150 μm.
[0144] Comparative Example 2
[0145] A polymer electrolyte was prepared by adding an isocyanate crosslinker and a lithium salt to polythiourea. 0.2 g (100 parts by weight) of PTU prepared in the manufacturing example was dissolved in 2 mL of DMF, 0.025 g (12.5 parts by weight) of PHDI (poly(hexamethylene diisocyanate); viscosity: 1300-2200 cP (25°C)) and 0.001 g of DD (dibutyltin dilaurate) were added, and the mixture was stirred evenly. 0.06 g (30 parts by weight) of LiTFSI (lithium bis(trifluoromethanesulfonyl imide)) was then added. The mixture was placed on a Teflon plate (2×4 cm 2), degassed and dried in a vacuum oven at 30° C., dried in a vacuum oven at 60° C. for 24 hours, and cured at 100° C. for 24 hours to produce a solid electrolyte membrane with a thickness of 150 μm.
[0146] Comparative Example 3
[0147] A polymer electrolyte was prepared by adding an isocyanate crosslinker and a lithium salt to polythiourea. 0.2 g (100 parts by weight) of PTU prepared in the manufacturing example was dissolved in 2 mL of DMF, 0.002 g (1 part by weight) of PHDI (poly(hexamethylene diisocyanate); viscosity: 1300-2200 cP (25°C)) and 0.001 g of DD (dibutyltin dilaurate) were added, and the mixture was stirred evenly. 0.125 g (62.5 parts by weight) of LiTFSI (lithium bis(trifluoromethanesulfonyl imide)) was then added. The mixture was placed on a Teflon plate (2×4 cm 2 ), degassed and dried in a vacuum oven at 30° C., dried in a vacuum oven at 60° C. for 24 hours, and cured at 100° C. for 24 hours to produce a solid electrolyte membrane with a thickness of 150 μm.
[0148] Comparative Example 4
[0149] A polymer electrolyte was prepared by adding an isocyanate crosslinker and a lithium salt to polythiourea. 0.2 g (100 parts by weight) of PTU prepared in the manufacturing example was dissolved in 2 mL of DMF, 0.06 g (30 parts by weight) of PHDI (poly(hexamethylene diisocyanate); viscosity: 1300-2200 cP (25°C)) and 0.001 g of DD (dibutyltin dilaurate) were added, and the mixture was stirred evenly. 0.125 g (62.5 parts by weight) of LiTFSI (lithium bis(trifluoromethanesulfonyl imide)) was then added. The mixture was placed on a Teflon plate (2×4 cm 2 ), degassed and dried in a vacuum oven at 30° C., dried in a vacuum oven at 60° C. for 24 hours, and cured at 100° C. for 24 hours to produce a solid electrolyte membrane with a thickness of 150 μm.
[0150] Comparative Example 5
[0151] Polyethylene oxide (PEO; weight-average molecular weight: 400,000) was used as an ion-conductive polymer and LiTFSI was used as a lithium salt. 0.2 g (100 parts by weight) of polyethylene oxide and 0.125 g (62.5 parts by weight) of LiTFSI were mixed, mechanically mixed using a ball mill, and then pressed at a pressure of 9,000 kgf and a temperature of 170°C for 10 minutes to obtain a solid electrolyte membrane with a thickness of 150 μm.
[0152] Experimental Example 1: Confirmation of electrochemical characteristics
[0153] 1) Measure ionic conductivity
[0154] For the polymer electrolyte prepared previously, the ionic conductivity was calculated using electrochemical impedance spectroscopy (EIS) by mathematical formula 1. In the frequency range of 1 MHz to 1 Hz, the measurement was performed using an alternating current with an amplitude of 10 mV. During the measurement, stainless steel (SS) was used and a solid electrolyte membrane was stacked between two stainless steel (Steel Use Stainless; SUS) plates to produce a CR2032 button cell in the form of a symmetrical cell (SS / SPE / SS). The impedance of the CR2032 button cell was measured using an Ivium n-Stat electrochemical analyzer, and the resistance of the bulk electrolyte was calculated from the intersection of the semicircle or straight line of the impedance trace and the real axis, and the ionic conductivity of the solid electrolyte membrane was calculated from the area and thickness of the sample. The Nyquist plot of the solid electrolyte of Example 1 is shown as follows: Figure 1 As shown, the ionic conductivity of the solid electrolytes of Examples 1 to 5 and Comparative Examples 1 to 5 was calculated by Mathematical Formula 1 and is shown in Table 1 below.
[0155] [Mathematical formula 1]
[0156]
[0157] σ: ionic conductivity (S / cmm)
[0158] R: The intersection of the impedance trace and the real axis
[0159] A: Area of solid polymer electrolyte membrane
[0160] t: thickness of solid polymer electrolyte membrane
[0161] 2) Measuring electrochemical stability
[0162] To measure the electrochemical stability, a coin cell was fabricated by inserting the fabricated solid electrolyte membrane between SUS as a measuring electrode and lithium metal as a counter electrode. Electrochemical measurements were performed by linear sweep voltammetry (LSV) at a scan rate of 10 mV / s up to 6 V. Figure 2Table 1 shows the LSV measurement results of the solid electrolyte produced in Example 1, and the electrochemical stabilities of Examples 1 to 5 and Comparative Examples 1 to 5.
[0163] 3) Measure lithium transference number (LTN)
[0164] The lithium cation mobility of the solid electrolytes produced in the above examples and comparative examples was measured using an Ivium n-Stat electrochemical analyzer with an applied voltage of 10 mV. The measurements were performed using a symmetrical cell (Li / SPE / Li) configuration, with the solid electrolyte placed between lithium metal disks. LTN can be calculated using Equation 2.
[0165] [Mathematical formula 2]
[0166] LTN=I ss (V-I0R0) / I0(VI ss R ss )
[0167] I0: initial current
[0168] I ss : Post-polarization current
[0169] R0: resistance before polarization
[0170] R ss : Resistance after polarization
[0171] Figure 3 The LTN measurement results of Example 1 are shown, and the LTNs of Examples 1 to 5 and Comparative Examples 1 to 5 are shown in Table 1.
[0172] [surface]]
[0173]
[0174] As shown in Table 1, it can be seen that the solid electrolytes of Examples 1 to 5 within the content range of the present invention have higher ion conductivity than the solid electrolytes of Comparative Examples 1, 2, and 4 outside the content range of the present invention. In addition, it can be confirmed that the isocyanate content of Comparative Example 3 is extremely low, making it difficult to form a film.
[0175] Furthermore, the solid electrolytes of Examples 1 to 5 exhibited higher ionic conductivity than the solid electrolyte of Comparative Example 5. This is because the irregularities between the polymer chains, due to the zigzag arrangement of thiourea, facilitate segmental motion of the polymer chains, resulting in high ionic conductivity. In contrast, the high crystallinity between the polymer chains of Comparative Example 1 hindered the transfer of lithium ions, resulting in low ionic conductivity.
[0176] In terms of electrochemical stability, it can be seen that the electrochemical stability of the solid electrolytes of Examples 1 to 5 within the content range of the present invention is greater than or equal to the solid electrolytes of Comparative Examples 1, 2 and 4 outside the content range of the present invention.
[0177] Furthermore, it can be seen that Examples 1 to 5 exhibited higher electrochemical stability than Comparative Example 5. This is because the polymer chains are electrochemically stable and have a cross-linked structure, thus being stable in oxidation and reduction reactions. In contrast, the polyethylene oxide-based electrolyte in Comparative Example 1 is susceptible to redox reactions due to the presence of hydroxyl groups at its terminals, and therefore exhibited lower electrochemical stability than the Examples.
[0178] In terms of the LTN results, it can be seen that the LTN of the solid electrolytes of Examples 1 to 5 within the content range of the present invention is greater than or equal to the solid electrolytes of Comparative Examples 1, 2, and 4 outside the content range of the present invention.
[0179] Furthermore, it can be seen that Examples 1 to 5 exhibit higher LTNs than Comparative Example 5. This is because the strong binding between the thiourea group and the anion of the lithium salt makes the lithium salt relatively easy to dissociate, thereby making the free lithium ions more likely to exist stably, resulting in a high LTN. In contrast, the electrolyte of the comparative example lacks characteristic groups capable of bonding with anions in the polymer chain, which makes it easier for the lithium salt to exist in the form of ion pairs, resulting in a low LTN.
[0180] Experimental Example 2: Measuring the Topological Freezing Transition Temperature
[0181] In order to quantitatively determine whether the solid electrolyte of the present invention exhibits vitrimer properties, a dilatometric test was performed by DMA in iso-stress mode. The test was performed by TA Instruments DMA Q850. The solid electrolyte of Example 1 was cut into a film (ca. 30 mm (L) × 5 mm (W) × 0.5 mm (T)) shape and used as a test piece. The test piece was cooled from room temperature to -20°C at a frequency of 1 Hz and a force of 1 kPa, and then cooled at 3°C min in a nitrogen atmosphere. -1 The temperature was raised to 160°C at a rate of .
[0182] Figure 4 is a graph showing the results of the expansion measurement experiment. Figure 4 , it can be seen that the glass transition temperature (Tg) is confirmed at around 28 degrees, and the topological freezing transition temperature (Tv) appears at around 118 degrees.
[0183] The glass transition temperature (Tg) is the temperature at which the polymer chain transitions from a rigid state to a glassy state due to segmental motion, and the topological freezing transition temperature (Tv) is the temperature at which the material transitions from a viscoelastic solid to a viscoelastic liquid due to rapid bond exchange.
[0184] From the above results, it can be seen that obvious physical properties (transition temperatures) appear at different temperatures, and the solid electrolyte produced thereby exhibits glass-like polymer properties.
[0185] Figure 5 is a picture of the experimental process. Figure 5 As shown, it can be confirmed that the solid electrolyte of the present invention recovers its original shape by reshaping when all the solvent is removed after casting. Therefore, it can be confirmed that the solid electrolyte of the present invention has self-repairing ability.
[0186] While the embodiments of the present invention have been described in detail above, the present invention is not limited to the embodiments and accompanying drawings, but is defined by the appended claims. Therefore, within the scope of the technical concept of the present invention as described in the claims, those skilled in the art will be able to make various substitutions, modifications, and alterations, all of which fall within the scope of the present invention.
[0187] Industrial Applicability
[0188] The lithium secondary battery including the solid electrolyte of the present invention has excellent output characteristics at low temperatures and excellent electrochemical stability and safety, and therefore can be used in electric vehicles and the like.
Claims
1. A solid electrolyte composition comprising: An amine compound represented by Chemical Formula 1; Polyfunctional isocyanates; and lithium salts, in, Based on 100 parts by weight of the amine compound, the content of the lithium salt is 40 to 80 parts by weight. [Chemical Formula 1] In the chemical formula 1, L1 and L2 each independently include a group selected from C1-C 12 Alkylene or heteroalkylene, C3-C 16 Cycloalkylene or heterocycloalkylene, C6-C 16 Arylene or heteroarylene and At least one of and , wherein n is a natural number in the range of 1 to 5000, and m is a natural number in the range of 1 to 200.
2. The solid electrolyte composition according to claim 1, wherein The polyfunctional isocyanate is at least one selected from triphenylmethane-4,4,4-triisocyanate, 1,3,5-triisocyanate-2-methylbenzene, tris(6-isocyanatehexyl)isocyanurate, 1,3,5-triisocyanate-2,4,6-trimethylbenzene and poly(hexamethylene diisocyanate).
3. The solid electrolyte composition according to claim 1, wherein Based on 100 parts by weight of the amine compound, the content of the multifunctional isocyanate is 5 to 20 parts by weight.
4. The solid electrolyte composition according to claim 1, wherein The lithium salt includes one or more selected from lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium nitrate (LiNO3) and lithium hexafluorophosphate (LiPF6). 5 . A solid electrolyte comprising a cured product of the solid electrolyte composition according to claim 1 .
6. The solid electrolyte according to claim 5, wherein The cured product has at least two inflection points in a curve of thermal strain versus temperature measured by dilatometry.
7. The solid electrolyte according to claim 5, wherein The cured product has a topological freezing transition temperature (Tv) higher than the glass transition temperature (Tg) measured by dilatometry.
8. A lithium secondary battery comprising: The solid electrolyte according to any one of claims 5 to 7; a positive electrode; and a negative electrode.